The effects of chromium picolinate on glucose and lipid metabolism in running rats - Pala, Ragip; Sari, Mehmet Akif; Erten, Fusun; Er, Besir; Tuzcu, Mehmet; Orhan, Cemal; Şahin, Kazım (Elsevier Gmbh, 2020)
Background: Chromium picolinate (CrPic) is commonly used to reduce muscle fatigue after exercise. We aimed to elucidate the effects of CrPic on glucose and lipid metabolism and the expression of glucose transporters in exercised rats. Methods: Forty-two male Wistar rats (8-week-old) were distributed into six groups (n=7) as follows: Control, CrPic, Chronic Exercise (CEx), CEx + CrPic, Acute Exercise (AEx), and AEx + CrPic. CEx consists of 30 m/min, 30 min/day, and 5 days/week for 6 weeks. CrPic was supplemented at 400 mu g elemental Cr/kg of diet for 6 weeks. In the AEx groups, animals were run on the treadmill at 30 m/min until exhaustion. Results: CEx significantly lowered blood glucose (BG), total cholesterol (TC) and triglyceride (TG) levels, but elevated insulin concentration (IC), compared with control (P<0.05). CEx significantly decreased the level of malondialdehyde (MDA) in the serum, liver, and muscle while AEx elevated it (P<0.001 for all). CrPic significantly decreased BG, TC, TG levels, and increased IC with a remarkable effect in CEx rats (P<0.01). CrPic also significantly reduced serum, liver, and muscle MDA levels (P<0.001). Both AEx and CEx increased the expression of liver glucose transporter 2 (GLUT-2) and muscle GLUT-4 with the highest level in CEx rats (P<0.05). Moreover, CrPic supplementation significantly elevated GLUT-2 and GLUT-4 expressions in the liver and muscle of sedentary and exercise-treated rats (P< 0.05). Conclusion: CrPic improves various metabolic parameters and reduces oxidative stress in CEx and AEx rats by decreasing BG, TC, TG, MDA levels in serum and elevating GLUT-2 and GLUT-4 expression in the liver and muscle samples. The efficacy of CrPic was more pronounced in CEx rats.
Keywords: Chromium picolinate; Glucose metabolism; Lipid metabolism; Oxidative stress; Exercise